Adjunctive application of antimicrobial photodynamic therapy in the prevention of medication-related osteonecrosis of the jaw following dentoalveolar surgery: A case series - Poli, Pier Paolo; Souza, Francisley Ávila [UNESP]; Ferrario, Susanna; Maiorana, Carlo (Elsevier, 2019)
Background: Medication-related osteonecrosis of the jaw (MRONJ) is a debilitating complication strongly associated to antiresorptive agents. The present study aimed to describe the use of antimicrobial photodynamic therapy (aPDT) in the prevention of MRONJ. Methods: The sample consisted of 11 non-oncologic osteoporotic subjects in therapy with non-intravenous antiresorptive agents, requiring tooth extractions and/or implant removal. After minimally invasive surgical extractions, each alveolar socket was debrided and bony edges were smoothened. At this point, aPDT was performed using methylene blue-based phenothiazine chloride dye irradiated with a hand-held 100 mW diode laser with a wavelength of 660 ± 10 nm. Flaps were sutured to achieve first intention closure. Soft tissue healing was promoted with weekly applications of low-level laser therapy for 6 weeks. Recall visits were scheduled weekly for the first two months and monthly thereafter up to 6 months. At the 6-month appointment, healing was assessed clinically and radiographically. Results: A total of 62 surgical extractions were performed in both jaws, including 51 natural elements and 11 dental implants. No intraoperative complications were observed. Immediate post-operative period was generally uneventful except for mild pain and ecchymosis that occurred rarely and resolved spontaneously. Healing proceeded uneventfully, with no clinical or radiological prodromal manifestations of MRONJ up to the latest follow-up visit. Conclusions: aPDT might constitute a promising preventive treatment to reduce the risk of MRONJ in non-oncologic osteoporotic patients treated with non-intravenous antiresorptive agents that underwent dentoalveolar surgery.
Keywords: Antimicrobial photodynamic therapy; Antiresorptive agents; Dentoalveolar surgery; Osteonecrosis; Peri-implantitis